VIBES A vibration-based data acquisition system for structural health monitoring - Austria, Jose Angelo C.; Bunagan, Aldrich C.; Moraleja, Lemuel G. (2010)
Most infrastructure used in order to sustain social and economic stabilities in different countries have been built years ago and are already in a state of deterioration. With the current economic crisis, countries must find ways to wisely manage and maintain these assets in order to extend the useful lives of structures. One way to address this problem is through the application of technologies from the rapidly developing field of Structural Health Monitoring (SHM). One approach used in SHM is the use of vibration-based monitoring. Although systems that are used to monitor the health of a structure based on changes in its dynamic characteristics already exist, the equipment used for sensing structural vibrations are not readily available in the Philippines. Most, if not all, come from abroad and are expensive. Having a cost-effective and easy-to-use system available for use in our own country will save a lot of resources such as time, money, and possibly the lives of many Filipinos. This project aims to develop a cost-effective data acquisition system that will aid in the analysis and diagnosis of structure's health. The data acquisition system is composed of three main parts: sensor nodes, master node and a Graphical User Interface (GUI). The sensor nodes, mounted directly on the structure, contains a microcontroller and a tri-axial accelerometer that is used to measure vibrations. Measurements taken in each node are sent to the master node using a Controller Area Network (CAN) bus. Data gathered by the master node are sent to the base station (PC) through the Universal Serial Bus (USB) which will connect, store, process and display data. A Python-based GUI was developed for data visualization, network configuration. The system was tested on different columns in the College of Engineering Building.
Thesis (B.S. Electronics and Communications Engineering)-- University of the Philippines, Diliman
Keywords: Automatic data collection systems; Structural health monitoring; Buildings -- Vibration; VIBES (computer software).